Electrically evoked compound action potential in children following cochlear implantation and its correlation with cochlear nerve diameter - Das, Aparna; Alexander, Arun; Sreenivasan, Anuprasad; Ganesan, Sivaraman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The study evaluated changes in the threshold of ECAP recorded during cochlear implantation, at switch on, after three months and six months following cochlear implantation. It further assessed the correlation between the ECAP threshold with T and C levels and the cochlear nerve diameter measured preoperatively. Methods: A prospective study of 42 prelingually deaf children who underwent cochlear implantation was conducted. The ECAP threshold values intra-operatively, at switch on, three months and six months were recorded and analysed. The T and C levels were assessed six months postoperatively, and correlation with the ECAP threshold was analysed. The diameter of the cochlear nerve was recorded, and its correlation with the ECAP threshold was determined. Results: Over six months, the basal, central and apical electrodes showed a statistically significant reduction in ECAP threshold of 11.64%, 4.67% and 25.81%, respectively, in candidates implanted with Advanced Bionics implant and 18.89%, 12.78% and 14.08%, respectively in candidates implanted with Nucleus implant. The ECAP thresholds were lower for the apical electrodes. No correlation was found between the ECAP threshold and T and C levels. A correlation between the cochlear nerve diameter and ECAP was not statistically significant. Conclusions: There was a statistically significant change in the ECAP threshold over six months. There was no statistically significant correlation between the ECAP thresholds and T and C levels. The value of ECAP thresholds to measure C and T values need to be relooked. There was no correlation between the cochlear nerve diameter and the ECAP threshold.